In vitro evaluation of the precision of working casts for implant-supported restoration with multiple abutments - Anderson Almeida Castilho; Alberto Noriyuki Kojima; Sarina Maciel Braga Pereira; Diego Klee de Vasconcellos; Marcos Koiti Itinoche; Renata Faria; Marco Antonio Bottino (University of São Paulo, 2007)
OBJECTIVE: The purpose of this study was to compare the accuracy of two working cast fabrication techniques using strain-gauge analysis. METHODS: Two working cast fabrication methods were evaluated. Based on a master model, 20 working casts were fabricated by means of an indirect impression technique using polyether after splinting the square transfer copings with acrylic resin. Specimens were assigned to 2 groups (n=10): Group A (GA): type IV dental stone was poured around the abutment analogs in the conventional way; Group B (GB), the dental stone was poured in two stages. Spacers were used over the abutment analogs (rubber tubes) and type IV dental stone was poured around the abutment analogs in the conventional way. After the stone had hardened completely, the spacers were removed and more stone was inserted in the spaces created. Six strain-gauges (Excel Ltd.), positioned in a cast bar, which was dimensionally accurate (perfect fit) to the master model, recorded the microstrains generated by each specimen. Data were analyzed statistically by the variance analysis (ANOVA) and Tukey's test (Î±= 5%). RESULTS: The microstrain values (µepsilon) were (mean±SD): GA: 263.7±109.07µepsilon, and GB: 193.73±78.83µepsilon. CONCLUSION: There was no statistical difference between the two methods studied.